Integration of Russia and Mongolia: Geopolitical and Geoeconomic Aspects - Irina Vladimirovna Zeleneva (Управленческое консультирование, 2018)
The author studies integration of Russia and Mongolia. Deepening integration between Russia and Mongolia is determined not only by the economic and social development of both countries, but also by the preservation of civilizational identity. The article also analyzes the role of energy cooperation between Russia and Mongolia. The expansion of Eurasian integration will contribute to the deepening of cooperation between Eurasian Economic Union and Mongolia. The author investigates the opportunity for trilateral cooperation between Russia, Mongolia and China. This the format of cooperation will assist in avoiding the loss of identity and to promote balanced and sustainable economic and political development of Russia and Mongolia.